Challenges and Possibilities of English: Speaking Back to the Centre. Issue 3 (3rd July 2019) - Anwar, Desvalini
ABSTRACT: This article emerges out of my autobiography as an English language educator and the conversations that I had with three other English teachers in universities in Padang, Indonesia. These conversations formed the core of my doctoral thesis, in which I used Benedict Anderson and Edward Said to theorise our situation as English educators working in a postcolonial policy setting. Our conversations reflected our efforts to account for the tensions and contradictions that we have experienced (and continue to experience) in learning and teaching English in Indonesia. For all the differences between our pedagogies, our teaching practices highlight our efforts to subvert and turn our traditional classroom and monologues into a contact zone where our students willingly engage in dialogue with the text they read – constructing identities that are personally meaningful to them.